1996
DOI: 10.1074/jbc.271.49.31549
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Enzymatic Activities of Topoisomerase IV and DNA Gyrase from Escherichia coli

Abstract: DNA gyrase and topoisomerase IV (Topo IV) have distinct roles as unlinking enzymes during DNA replication despite 40% sequence identity between them. DNA gyrase unlinks replicating DNA by introducing negative supercoils while Topo IV decatenates the two daughter molecules. For this study, we measured the rates of unlinking of various topoisomers of DNA by DNA gyrase and Topo IV. Each enzyme has marked preferences for certain strand-passage reactions. DNA gyrase is a relatively poor decatenase, catalyzing stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 62 publications
5
122
0
1
Order By: Relevance
“…To further establish that the large products were catenated DNA rings, a preparation of catenated DNA was treated with Topo IV, which is a very active decatenating enzyme (21,22). In the presence of very low concentrations of Topo IV (125 pM), the large DNA products were partially resolved into intermediate bands and the monomer gDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further establish that the large products were catenated DNA rings, a preparation of catenated DNA was treated with Topo IV, which is a very active decatenating enzyme (21,22). In the presence of very low concentrations of Topo IV (125 pM), the large DNA products were partially resolved into intermediate bands and the monomer gDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of DNA supercoiling on DNA unknotting by bacterial topoisomerase IV was investigated in 1996 by Ullsperger and Cozzarelli (27), who concluded that supercoiling of knots did not cause an appreciable increase in the rate of their unknotting by Topo IV. However, a closer look at their experimental data reveals that, although the unknotting rate of complex knots with nine crossings appears to be unaffected by supercoiling, there is a clear effect on unknotting of simple knots.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies further sustain its role as a decatenase by demonstrating that, through the interaction with a septal ring protein FtsK, Topo IV is only accessible to DNA at the end of replication (14). Because the decatenating activity of Topo IV is stimulated by (Ϫ) superhelical density, the two enzymes appear to work in concert to complete replication (15).…”
mentioning
confidence: 99%